BIBLIOMETRIC ANALYSIS AND MAPPING OF ARTICLES PUBLISHED ON THE DEGREE OF URBANISATION METHOD IN THE SCOPUS DATABASE - Endrawati Fatimah; Ramadhani Yanidar; Rissa Yuliana Dwi Jayanti (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
The United Nations Statistical Commission agreed in March 2020 to start using the Degree of Urbanisation as a method to delineate cities, urban, and rural areas to enable international statistical comparisons. The decision consequently promotes countries to change or align their classification and/or methods of urbanisation delineation. This is expected to increase the number of studies with “degree of urbanisation” or “urban classification” keywords around the world in line with the implementation of the method. Aim: This study aims to determine the research trends on the degree of urbanisation in the Scopus database from the year 2013 to 2022. Methodology and results: The bibliometric method was applied through the VOSviewer software (version 1.6.18. Leiden University, Leiden, Netherlands) for the analysis. The findings showed that the topics related to the degree of urbanization are underrepresented in terms of the number of publications and contributing nations though the trend in the number of articles published in the Scopus database has annually increased from 2017-2021. Conclusion, significance and impact study: This implies there is a lot of potential regarding the publication of studies on the concept of “degree of urbanization”